The Benefits of Implementing Task-Based Learning in Speaking Class - Hilma Safitri Safitri (Arden Jaya Publisher, 2026)
This article aims to provide some information regarding how task-based learning is implemented in a classroom. Due to the luck of language knowledge and confidence, some students are unable to speak in class by using English. Moreover, the students need to have motivation in order to speak confidently. Hence, task-based learning is suitable in order for them to interact by using English. By using task-based learning they can have some tasks such as turn taking, information gap activity, simulation, role play and drama. It is hoped that they feel motivated when implementing various tasks. The methods applied is to use some theories regarding task-based learning from various sources in order to provide the information in several steps that are 1) the focus and scope of the study were determined, 2) relevant literature was selected, organized, and synthesized, 3) the findings from the literature review were used to develop the analysis and arguments. The findings indicate that task-based learning 1) boots the students’ motivation in speaking, 2) facilitates the student in speaking in which they feel comfortable and relax when leering speaking in class, and 3) enhances the students language skills in which they manage to learn in terms pf speaking, reading, listening and writing.